Karakteristik Pasien Nyeri Punggung Bawah di Poliklinik Saraf RSUD Arifin Achmad Provinsi Riau - Maryanti, Yossi; Darmawi, Darmawi; Zikra, Izza Fattalia; Khairussyifa, Najmi; Arenja, Regina Trisya; Aini, Sabrina (Jurnal Ilmu Kedokteran, 2025)
Low back pain (LBP) is defined as discomfort felt between the lower costal margin and the inferior gluteal fold, and it is one of the most common complaints that bring people to seek medical attention. The World Health Organization (WHO) in 2017 reported that LBP ranked second as a global cause of disability in musculoskeletal system issues, and according to WHO data from 2022, 619 million people worldwide suffer from LBP. This study aims to identify the characteristics of patients with low back pain who seek treatment at the Neurology Polyclinic Arifin Achmad General Hospital of Riau Province. The characteristics examined include age, gender, work duration, body mass index (BMI), waist-hip ratio (WHR), pain severity, and disability level in daily activities. This is a descriptive observational study with a cross-sectional design, conducted at the Neurology Polyclinic Arifin Achmad General Hospital of Riau Province, from July to September 2024. Data were collected through guided interviews using structured questionnaires, the numeric rating scale (NRS), and the oswestry disability index (ODI), as well as anthropometric measurements. The frequency distribution of each characteristic was analyzed using SPSS. The sample was collected, consisting of 50 patients. The results showed that the majority of low back pain patients were aged 35-55 years (54%), female (62%), worked ≥ 8 hours per day (58%), had a BMI in the obese category (54%), had a WHR in the central obesity category (52%), experienced severe pain (52%), and had a severe disability (58%).